Acanthosaura aurantiacrista (Squamata: Agamidae), a new long horn lizard from northern Thailand - Trivalairat, Poramad (Biodivers Data J, 2020)
BACKGROUND: In Thailand, five species of Acanthosaura have been recorded so far, including Acanthosaura armata from the southern region, A. cardamomensis from the eastern region, A. crucigera from the western region, A. lepidogaster from the northern region and A. phuketensis from the Phuket Island and south-western region. However, comprehensive studies of diversity patterns and distribution of Acanthosaura are still lacking in some areas and need further information for designating areas of special conservation importance and nature protection planning in Thailand. NEW INFORMATION: Acanthosaura aurantiacrista is a new species of long-horned lizard of the genus Acanthosaura from northern Thailand. It is distinguished from all other species of Acanthosaura by a dagger-like nuchal spine with yellowish-orange colouration in females, bright yellow colouration in males and a combination of other morphological characters: a greater tail length to snout-vent length ratio; a larger postorbital spine, nuchal spine, dorsal spine and occipital spine compared to its head length; a smaller diastema to snout-vent length ratio; a greater number of subdigital lamellae on the fourth finger and fourth toe; and a larger gular pouch than other Acanthosaura species. Analysis of mitochondrial ND2 gene sequences revealed a sister clade between the A. aurantiacrista lineage and the A. crucigera lineage with a 100% probability of divergence, according to Bayesian analysis and strong support value for Maximum Likelihood analysis. The pairwise distance ranged from 13.8-15.0% between A. aurantiacrista and A. cardamomensis, 10.9-14.5% between A. aurantiacrista and A. crucigera and 0-1.2% amongst A. aurantiacrista populations. The discovery of this lizard increases the known endemic herpetological diversity and underscores the importance of conservation in the mountain rainforest region of northern Thailand.